Media and everyday practices: Rethinking daily life in a mediated society - Rianto, Puji (Jurnal Komunikasi, 2026)
Historical studies of media show that the advent of communication technology has transformed human communication, the ways in which people interact and the organization of human life (Briggs & Burke, 2000). The scope and depth of change heavily depend on the ability of communication technologies or media to penetrate people’s lives. Therefore, the scale and scope of change within a society will vary. The greater the penetration of communication technologies in society, the stronger their influence on how people communicate and organize their social lives. When we look at the pace of social change, the pervasive influence of communication technology and media is increasing. The implications of media technology—from the era of writing (writing culture), through print (print culture) and electronic (electronic culture), to the digital age (digital culture)— continue to grow stronger and more pervasive, leaving almost no space where people can escape the presence of media. In this context, Grossberg et al. (2006, p. 43) draw the following interesting conclusion: “... if written media centralized and made knowledge hierarchical, and then the printing press began a process of dispersion and democratization of knowledge, the electronic media have drastically accelerated both of these trends.”